Publishing Trends of Informal Lithuanian Youth Publications –Fanzines – at the End of the 20th Century and the Beginning of the 21st Century - Kairaitytė-Užupė, Aušra (Knygotyra, 2024)
This article analyzes Lithuanian youth subcultural group publications – fanzines (zines) – which have not yet received broader attention from researchers. Paper fanzines started to be created at the end of the 20th century and became popular in the 1990s, spreading Western culture ideas and changing the political, and socio-cultural environment in Lithuania along with technological copying and reproduction possibilities. Using resources from Lithuania’s Youth Culture Digital Archive “Lithuanian Zine Collection” and additionally collected sources, the article analyzes the trends in the creation and publishing of fanzines. By comparing the publishing similarities and differences of fanzines attributed to different subcultural groups, the aim is to understand the cultural context of these publications, their relationship with readers, and the publishing possibilities of fanzine creators. The study applies descriptive metadata analysis and systematization of fanzines, as well as ethnographic research methods (targeted interview, questionnaire, and qualitative interviews with fanzine authors, publishers, and collectors). The research results showed that in Lithuania, mainly in the 1990s, metal music fanzine authors, unlike punks and science fiction fans, created more publications written in English. Metal music fanzines were characterized by greater volume. Science fiction fans’ publications differed from those of metalheads and punks by a greater number of continuous issues and fewer one-time publications. Authors of fanzines associated with punk ideology mostly chose to independently reproduce publications using a copying machine, while creators of metal music and science fiction fanzines more often used professional printing services. The language used in fanzines and its style helped to form a close relationship with readers, revealed the identity traits of subcultural groups, and helped metal music fanzine authors to integrate into the international fanzine culture context. Seeking independence and individuality, fanzine creators disregarded professional publishing standards. Fanzine publishing depended on individual choice, motivation, creativity, reader interest, and technological possibilities (publication reproduction, layout). Fanzines created in Lithuania became one of the main forms of idea dissemination, creative freedom, and self-expression for alternative youth communication.